A multi-analytical approach for pore structure assessment in historic lime mortars. (22nd February 2021) - Divya Rani, S.; Rahul, A.V.; Santhanam, Manu
Highlights: Samples of historic lime mortars assessed for pore structure using different techniques. Automation of porosity determination from SEM and X-ray tomography images by overflow technique. SEM and XRT limited in their ability due to the resolution, although they can capture closed pores. Water sorptivity and MIP give comparable results for systems with coarse porosity. Abstract: Porosity of a mortar significantly influences its mechanical characteristics as well as durability. To ensure compatibility while designing a repair mortar for historic masonry, it is important to have both a qualitative and quantitative description of the pore structure. In this paper, we present the porosity investigations of two types of historic lime mortars by scanning electron microscopy (SEM), X-ray tomography (XRT), water sorptivity and mercury intrusion porosimetry (MIP). The overflow method is used to quantify the porosity from the frames/slices obtained from the SEM/XRT respectively. Different techniques measure different aspects of the pore structure and a comparison of results from different analytical methods allowed overcoming their specific limitations and achieving a better knowledge of the pore system of historic mortars.